Anthocyanins-loaded nanocomplexes comprising casein and carboxymethyl cellulose: stability, antioxidant capacity, and bioaccessibility. (January 2022) - Cui, Huijun; Si, Xu; Tian, Jinlong; Lang, Yuxi; Gao, Ningxuan; Tan, Hui; Bian, Yuanyuan; Zang, Zhihuan; Jiang, Qiao; Bao, Yiwen; Li, Bin
Abstract: Anthocyanins (ACNs) have attracted considerable research attention because of their excellent biological activities, but their low stability and bioavailability limit their applications. The objective of this study was to prepare nanocomplexes by the self-assembly of casein (CA) and carboxymethyl cellulose (CMC) to encapsulate and stabilize ACNs. Three types of nanocomplexes (Complex Ⅰ, Ⅱ, and Ⅲ) were formed, with some differences in particle size, polydispersity index (PDI), and encapsulation efficiency (EE) due to the different adding sequences of the raw materials. Complex III (CA-CMC-ACNs) had the smallest size (209.9 nm) and PDI (0.327), while Complex II (CMC-ACNs-CA) had the highest EE (44.23%). Scanning electron microscopy (SEM) revealed that the ACNs-loaded nanocomplexes had a coarser spherical structure than the empty nanocomplexes. Fourier-transform infrared (FTIR) spectroscopy and differential scanning calorimetry (DSC) confirmed that ACNs-loaded nanocomplexes were formed by electrostatic interactions and hydrogen bonding. The nanocomplexes, particularly Complex II, effectively attenuated the degradation of ACNs under light, thermal, or ascorbic acid treatment. Complex II also showed the highest ACNs retention rate, bioaccessibility, and antioxidant capacity after simulated digestion. These results emphasized that the addition of raw materials in different sequences is an important factor influencing the particle size and EE of nanocomplexes, which in turn affected their protection of ACNs. This study provided great potential for the applicable value in the development of stabilizing anthocyanins. Graphical abstract: Image 1 Highlights: Nanocomplexes prepared with CA and CMC improved environmental stabilities of ACNs. Nanocomplexes enhanced ACNs' digestive resistance and bioaccessibility. Complex Ⅱ (CMC-ACNs-CA) performed best in EE and stability. Complex Ⅲ (CMC- CA-ACNs) had smallest particle size.